El Excentrico, 1973-06-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
June 5, 1973 [5 de junio de 1973]. No volume or issue number. Cover has a photograph of Mexican actresses Elsa Aguirre and Alma Rose Aguirre with El Excentrico columnist Maria Antonieta Hernandez